HUBUNGAN PEMAHAMAN KEPALA SEKOLAH TENTANG STANDAR PENGELOLAAN PAUD TERHADAP MANAJEMEN PESERTA DIDIK DI TK SEKECAMATAN BUKIT RAYA KOTA PEKANBARU - Ayustina Marsya; Zulkifli N Zulkifli N; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine the relationship between the principal's understanding of early childhood management standards and the management of students in Kindergarten in the Bukit Raya district of Pekanbaru City with statistical analysis methods, the data used in this study is primary data, primary data is data used directly from respondents. To be examined, the existing data cannot be interpreted, to be understood, it must be processed so that conclusions can be made using the Pearson Product Moment correlation test. The number of samples is 40 principals. The type of instrument used in this study is to use tests and questionnaires that will be distributed to the principal. Based on the results of the hypothesis test, there is a relationship between the principal's understanding of early childhood management standards and the management of students in Kindergarten in the Bukit Raya sub-district, Pekanbaru City. The value of tcount is 0.735 with sig 0.000, because sig < 0.05, it can be concluded that there is a significant relationship between the principal's understanding of PAUD management standards and student management. In the hypothesis test, it can be seen that tcount = 0.735 > ttable = 0.312. The relationship between Principal's Understanding of Early Childhood Management Standards and Student Management in Kindergarten in Bukit Raya District, Pekanbaru City is 54%. Key Words: Principal's Understanding of PAUD Management Standards, Student Management